1980
DOI: 10.1002/pssa.2210600202
|View full text |Cite
|
Sign up to set email alerts
|

The effect of thermal treatment on the electrical activity and mobility of dislocations in Si

Abstract: It is shown that the starting stresses for dislocation glide and their electrical activity are determined by the temperature, dislocation velocity, and distance moved upon bringing them to the starting position and, also, on the sample cooling rate after deformation. A correlation between starting stresses and dislocation donor center concentration is observed. It is shown that the result obtained is determined by the formation of complicated centers in the impurity atmospheres of both, mobile and immobile dis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
15
0
1

Year Published

1981
1981
2005
2005

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 46 publications
(16 citation statements)
references
References 20 publications
0
15
0
1
Order By: Relevance
“…Instead, it seems that in crystals with a high oxygen content, the concentration of dislocation related centers increases compared to FZ-Si samples or to Cz ones with a lower oxygen content. Thus, as shown in [8], dislocations can gather oxygen during their gliding through the crystal, even at temperatures as low as 600 C. Thus, oxygen could affect the formation of electrical and optical properties of dislocations. As shown in [14], dislocations after having covered a short distance are inactive, and for the formation of a conventional dislocation DLTS spectrum they should glide a distance, much shorter in Cz than in FZ-Si.…”
Section: Discussionmentioning
confidence: 96%
See 2 more Smart Citations
“…Instead, it seems that in crystals with a high oxygen content, the concentration of dislocation related centers increases compared to FZ-Si samples or to Cz ones with a lower oxygen content. Thus, as shown in [8], dislocations can gather oxygen during their gliding through the crystal, even at temperatures as low as 600 C. Thus, oxygen could affect the formation of electrical and optical properties of dislocations. As shown in [14], dislocations after having covered a short distance are inactive, and for the formation of a conventional dislocation DLTS spectrum they should glide a distance, much shorter in Cz than in FZ-Si.…”
Section: Discussionmentioning
confidence: 96%
“…However, the effect of oxygen has been the object of less attention although it is one of the most important impurities in Si. Nevertheless, it has been demonstrated that oxygen reduces the dislocation mobility [7] and leads to the formation of a starting stress [7,8]. It was shown [8] that oxygen can be gathered by moving dislocations even at 600 to 700 C and that its concentration in the dislocation atmosphere depends on the oxygen content as well as on the parameters of dislocation motion.…”
Section: Introductionmentioning
confidence: 98%
See 1 more Smart Citation
“…On the other hand the creation of donors in the vicinity of dislocations has been reported in Ref. [20]. It is important that these donors were more stable than usual TDs.…”
Section: Introductionmentioning
confidence: 95%
“…Processes of accumulation of impurities to dislocations resulting in static aging and locking them are studied experimentally [5][6][7]. Dynamic aspects of interaction between impurity subsystem and dislocations are less investigated (see, as an exception, [8]). …”
mentioning
confidence: 99%